Comparative studies of early childhood education and care: beyond methodological nationalism. Issue 3 (3rd July 2022) - Guevara, Jennifer
ABSTRACT : With early childhood inhabiting a firm position on policy agendas, an emerging global consensus acknowledges the need for research into early childhood education and care (ECEC) systems. However, standardised approaches to comparison dominate the field. These studies tend to be grounded in methodological nationalism, assuming nation states as the natural and necessary unit to study social phenomena. I argue the national unit is not sufficient to understand ECEC systems and that we need to consider subnational levels (district and local). Subnational approaches enable the reconstruction of the different actors and institutions at play in all levels of ECEC systems. This movement beyond methodological nationalism requires a shift towards integrated approaches and territorialised policy analysis. I illustrate my argument drawing on qualitative data from two subnational studies in Argentina. I discuss the conceptual and methodological implications for international comparison and comparative research in the early childhood field.